'Learning' and Learning at Euthydemus 275d–278d. Issue 2 (3rd April 2019) - Thomas, Christine J.
ABSTRACT: Earl y in Plato's Euthydemus, sophistical arguments threaten the intelligibility of the process of learning. According to M. M. McCabe, Socrates resists the sophists' arguments by resisting their problematic replacement model of change. The replacement model proposes that one item (e.g., an unlearned one) is simply replaced with a nonidentical item (e.g., a learned one). Socrates is said to endorse a rival metaphysics of temporally extended, teleologically structured activities. The rival model allows an enduring subject to survive 'aspect changes' by occupying distinct stages in a continuous, unified process. McCabe may be right that Socrates presupposes or favors a metaphysics of continuous, end-oriented activities. If so, there are independent reasons to strive to understand the teleological structure of the activity of learning. Nevertheless, I am not convinced that Socrates relies on such a metaphysics to resist the learning arguments at 275d—278d. I argue that Socrates appeals, instead, to the complexity of the learning process to recognize two distinct, yet related, uses of the term 'learning.' In order to resist the sophists' arguments, Socrates recommends attending to 'the correctness of names'. Socrates's disambiguating response is sufficient to dissolve the sophistical arguments while remaining compatible with a variety of metaphysics of individuals and activities.